(untitled) (Research, Society and Development, 2020)
Objective: In this scientific study, we aimed to evaluate genotoxic effects in rats (Rattus norvegicus), related to different periods of exposures to the LED curing light. Methodology: For the genotoxicity evaluation, the rats received lights from the LED photopolymerizer for 40 sec, 10 min and 7-and-a-half minutes, while the negative and positive control groups were treated with distilled water and cyclophosphamide by intraperitoneal, respectively. A sample of peripheral blood was collected from the animals for the comet assay. The bone marrow was collected from each rat for the micronucleus test. Results: It was observed that in the comet assay and micronucleus test, the animals exposed to LED for 10 min, showed genotoxic damage, and they have not presented toxicity degree in the periods of 40 sec and 7-and-a-half minutes. Conclusion: It is possible to conclude that, there was genotoxic effects on the animals’ teeth when exposed to the LED curing light in 10 min. However, in the periods of 40 sec, and 7- and-a-half minutes, have been not observed genotoxic effects. This means these times are safe for professional dentists in clinical care.